The purpose of this paper is to analyze and discuss preschool teachers’ supportive approaches when supporting parents within their profession. Questions addressed are; what kind of supporting approaches do preschool teachers practice to strengthen parents - Azaola, Marta C. (International Journal about Parents in Education, 2023)
This paper analyses home-school-community links from three different standpoints: education policies, schools and families. The paper provides empirical evidence on how education policies, schools and families operate in the Mexican context. Evidence from this study suggests that the interrelationship between these three standpoints is not equal and constant. Although it could be argued that ideally these should have a balanced relation, evidence from this study reveals that a bottom-up intervention is, in practice, more difficult to achieve considering that it is difficult for families to influence education policies and change school practices. The paper claims that studies on home-school-community links should critically explore the interrelation between education policies, schools and families in order to unveil inequalities within home-school-community links.